Managing Nigeria's Education amidst the Covid- 19 Pandemic Era: Implication on Educational Funding - Azi, Augustine Sambo (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022DO - 10.58709/niujss.v8i1.1403, 2022)
This theoretical paper examined the management of Nigeria's education amidst the COVID-19 pandemic era and its implication on educational funding. It was revealed in the paper that COVID-19 which is a disease with origin from China got into Nigeria in February, 2020. The Presence of the disease led to the closure of schools in Nigeria on the 19 th of March, 2020. This led to a disruption of educational activities in all learning institutions in the country. These disruptions affected learning modes, access to school related activities and parenting routines. The paper also revealed that the three main obstacles for learners in the midst of school shutdown were a lack of access to technology, an unsuitable home learning environment and a lack of access to learning materials. It was also revealed that the use of blended learning, innovative partnerships and accelerated digital skills through on line learning were used in managing education during the pandemic. Furthermore, revenue inflows dwindled for government, households and developmental partners in the midst of COVID-19 pandemic. This fall in revenue negatively affected the education sector in Nigeria. For Nigeria to overcome the challenges of COVID-19 and effectively manage the pandemic in the educational sector and its implication on educational funding, the paper recommended among others for the provision of infrastructure for learning, keeping students safe online, improved educational funding and reduction in taxes to educational institutions by government. Keywords: COVID-19, Education Sector, Funding, Pandemic